The Effect of Industrial Management Implementation on MSME Operational Performance in the Gresik Region - M. Azizul Khakim (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of management application on the company's operational performance which includes planning (planning), organizing (setting), leading (leadership), and controlling (controlling) on operational performance in Micro, Small, and Medium Enterprises (MSMEs). The subjects in this study were 50 Micro, Small, and Medium Enterprises (MSMEs) in Gresik. Another data source from this study was obtained through questionnaires distributed to owners and actors of Micro, Small, and Medium Enterprises (MSMEs). The data analysis method in this study uses multiple linear regression with the SPSS version 21 application. The results of this study can illustrate that industry management as a whole has a positive and significant effect on operational performance. Partially there is a positive and significant influence on planning, and organizing (setting). ), and controlling (controlling), but in this study leading (leadership) has a negative effect on operational performance but is not significant.